Features and Limitations of Fused Deposition Modelling (FDM) in Obtaining Textile-like Structures - Viktorija Diak; Andrii Diak (Tekstilec, 2024)
In contemporary production processes and customisation, 3D printing has emerged as a prominent method for prototyping. It offers flexibility to create objects of diverse shapes, structures, sizes and materials. However, integrating this technology into the textile industry to achieve textile-like structures poses challenges. The fused deposition modelling (FDM) method is currently the closest approach to prototyping such structures due to its ability to extrude monofilaments resembling traditional threads. Regrettably, attempts to produce structures with properties akin to textiles, including flexibility, durability, breathability, lightness and fineness, have been unsuccessful due to various limitations inherent in the technical setups of 3D printers. This study analyses the key features of FDM printing that determine the feasibility of achieving authentic textile-like printed structures while clarifying the underlying logic behind their future purpose. Our aim was to assist future researchers in achieving the production of thin 3D-printed fibres (diameter ~0.1 mm) regardless of structure type.